(untitled) (MAUSAM, 2023)
Impact of high-resolution Sea Surface Temperature (SST) derived from the Regional Ocean Modeling System (ROMS) on two intense vortices (Phailin and Hudhud) developed over the Bay of Bengal (BoB) are investigated. The validation of ROMS-SST with various observational datasets available over BoB showed a reasonably good correlation of greater than 0.90. The root mean square difference is around 0.40 °C. Instigating ROMS-SST as a lower boundary condition to the Advanced weather research (ARW) model improved the TC intensity and rainfall location for TC Phailin. A minor improvement is observed in the intensity of TC Hudhud. Still, with better replication of wind structure and rainfall location than the control experiment, which uses low-resolution Reynolds-SST from the global model output. This right sector peak of latent heat pattern matches better with the observed structure of deep convection observed from infrared satellite imagery for both TCs in the ROMS experiment as compared with the control experiment. However, the model simulated track for the ROMS-SST experiment did not improve the TC track for all the initial conditions for both the TCs. The present modeling study compliments the use of higher resolutions SST downscaled by a mesoscale regional ocean model for the TC simulations